2019
DOI: 10.1177/0021998319857112
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of poly(3-glycidoxypropyltrimethoxysilane) nanocomposite using organophilic montmorillonite clay (Mag-cetyltrimethylammonium)

Abstract: Nanocomposites of linear poly(3-glycidoxypropyltrimethoxysilane) based on Algerian natural organophilic clay: montmorillonite–cetyltrimethylammonium named Maghnite-CTA were prepared by enhancing the dispersion of the matrix polymer in sheets of the organoclay. The effect of the organoclay, used with different amounts (3, 5, and 7% by weight) and the preparation method were studied in order to determine and evaluate their structural, morphological and thermal properties. X-ray diffraction analysis of obtained n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…This also explains the beneficial effect of ultrasound on the dispersion of clay in the PLM matrix. The effect of ultrasound also gives better yields compared to the in-situ polymerization synthesis method [30].…”
Section: Characterization Of Nanocomposites (Plm-mag)mentioning
confidence: 99%
See 1 more Smart Citation
“…This also explains the beneficial effect of ultrasound on the dispersion of clay in the PLM matrix. The effect of ultrasound also gives better yields compared to the in-situ polymerization synthesis method [30].…”
Section: Characterization Of Nanocomposites (Plm-mag)mentioning
confidence: 99%
“…This behavior leads to a large dispersion of the clay sheets in the PLM matrix. It can be noted that the use of ultrasound for the synthesis of nanocomposites has a great advantage compared with classic methods which is take 24 h of reaction time [30].…”
Section: Characterization Of Nanocomposites (Plm-mag)mentioning
confidence: 99%
“…The use of organoclay (Mag-CTA + ) has an impact on the morphology of the prepared nanocomposites, especially in the dispersion of in-situ polymerization methods. For these reasons, several nanocomposites based on polymers and organoclay were prepared [ 20 , 21 , 22 , 23 , 24 ]. By reviewing the literature, we found that no previously published work has described the use of natural clay as a nano-reinforcing filler in the preparation of green-nanocomposites based on rosin-limonene copolymer.…”
Section: Introductionmentioning
confidence: 99%
“…To meet industry standards while respecting the environment, acids have been replaced by another clay-based ecocatalyst called Maghnite. The latter is of the montmorillonite type and has been the subject of several studies [14][15][16]. The clay layer has a hydrophilic character and metamorphoses into organoclay (surfactant) to facilitate the wetting of the polymer molecule on the clay surface [17,18].…”
Section: Introductionmentioning
confidence: 99%